PERANCANGAN KEY PERFORMANCE INDICATOR OPERATOR DAN FOREMAN DEPARTEMEN QUALITY CONTROL DI PT. X - Yenny Vebriana; Liem Yenny Bendatu (Jurnal Titra, 2014)
PT. X, is a bicycle company, tries to meet the needs of local and international con-sumers. Meeting the needs of the consumer must be accompanied with quality products espe-cially international standards. Thus, high skill employees both in production and Quality Control departments are in need. Key Performance Indicator (KPI) is one of the tools for measuring the staff skills. In this project we design the Key Performance Indicator s based on Balanced score card to the level of foreman and operators at Incoming Department and Assembly Department. Design of Key Performance Indicator s based on Balanced score card to the level of foreman and operators Department Incoming and Assembly consists of 2 perspectives which are customer per-spective and learning and growth perspective. Customer perspective is based on the work fore-man and operators with regard to the level of accuracy checking of goods that meet the standard specification while learning and growth perspective consists of two tests, i.e. written and practice tests. The test material for the Incoming Department foreman or operatorare namely checking part measurements, checking surface condition, standard specification, checking each part type, and knowledge of measuring instruments used. The test material for the Assembly Department foreman are namely knowledge of measuring instruments used, describing an assembly production line, the standard specification, assembly of bicycles in accordance with the function of each part.